1997
DOI: 10.1111/j.1365-2915.1997.tb00309.x
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of louping ill virus between infected and uninfected ticks co‐feeding on mountain hares

Abstract: Most of the data on oral infection of ticks by louping ill virus have been obtained from experiments in which animals were infected by syringe inoculation with infectious material. Using infected ticks to mimic the natural situation, we have demonstrated that louping ill (LI) virus transmission can occur from infected to uninfected Ixodes ricinus feeding in close proximity on mountain hares (Lepus timidus). Under these conditions the hares developed either low or undetectable viraemias. Highest prevalence of L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
72
0
2

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(76 citation statements)
references
References 12 publications
(7 reference statements)
2
72
0
2
Order By: Relevance
“…For example, louping ill infected ticks have been collected from wildlife that did not develop detectable viraemia (Jones et al, 1997). The lack of clinical disease in recipient animals may be due to an insufficient number of infected ticks being attached to them.…”
mentioning
confidence: 99%
“…For example, louping ill infected ticks have been collected from wildlife that did not develop detectable viraemia (Jones et al, 1997). The lack of clinical disease in recipient animals may be due to an insufficient number of infected ticks being attached to them.…”
mentioning
confidence: 99%
“…Jones et al (1997) showed that uninfected ticks became infected when they co-fed with Louping ill infected ticks on apparently non-viraemic wild-caught hares. NVT was reported also for Kyasanur Forest disease virus by soft tick Argas persicus on domestic chick (Singh et al, 1971).…”
Section: Non-viraemic Transmissionmentioning
confidence: 99%
“…Mountain hares (Lepus timidus) have been shown experimentally to allow LIV transmission nonviraemically between co-feeding ticks (Jones et al, 1997). As a result some grouse managers are conducting extensive culls of mountain hares in an effort to reduce LIV prevalence in red grouse.…”
Section: Control Strategies Of Louping Ill Virusmentioning
confidence: 99%